CHINESE LANGUAGE LEARNING IN ASIA AND THE ETHNIC IDENTITY OF THE CHINESE POSTERITY - Yutaka Otsuka (Jurnal Kependidikan, 2020)
This paper firstly overviews the historical changes of Chinese language and its education in four nations of Southeast Asia. These nations experienced the blank period when Chinese language was oppressed or forbidden to use by the ruler at the time, although length and austerity of the blank period differs from nation to nation. However, according as their relationship with People’s Republic of China in the international political arena has improved and economic exchanges have been vitalized, a different scene from previous era can be observed in the attitude towards overseas Chinese and their language. Questionnaire surveys were carried out for several years to make clear how the situation of Chinese language education looks like. Statistical analysis of the responses by nation and the comparison of responses from Chinese and non-Chinese youngsters leads us to some findings of how different conditions of each country give influence to the way Chinese language education is carried out and the consciousness and ethnic identity through language is being formed.